Perlindungan Konsumen Atas Jual Beli Produk Pakaian Di Marketplace Shopee Berdasarkan Doktrin Caveat Venditor - Tamana, Michelle; S, Hengki Firmanda; Samariadi, Samariadi (Peneliti.net, 2025)
The form of legal protection for consumers is outlined in Law Number 8 Year 1999 on Consumer Protection and Law Number 1 Year 2024 on Electronic Information and Transactions. Based on the doctrine of caveat venditor, sellers should be careful and cautious in selling products to consumers to protect consumers and prevent losses that can be caused by irresponsible sellers. However, the protection of consumer rights has not gone well. There are still many discrepancies between the type and quality of goods received by consumers and those promised by business actors as stated in the description of the products sold. Therefore, the research objectives of this thesis are first, consumer protection for buying and selling clothing products in the Shopee marketplace. Second, consumer protection that should be based on the doctrine of caveat venditor. This type of research can be classified into the type of sociological research. With the research location located in the online buying and selling site in the Shopee marketplace, while the population and sample are all parties related to the problem under study. This research uses data sources in the form of primary data and secondary data, and data collection techniques are carried out by means of interviews, questionnaires, and literature review. From the results of the problem research, there are two main things that can be concluded. First, consumer protection for buying and selling clothing products in the Shopee marketplace has not been implemented properly. Consumers often suffer losses due to products that do not match the claims of business actors. Second, consumer protection that should be based on the caveat venditor doctrine is manifested in the form of obligations of business actors in accordance with the caveat venditor doctrine, namely related to the quality and accurate and honest representation of goods, disclosure of information relevant to the product, responsibility for damage or loss, providing warranty or compensation to consumers who experience losses, and compliance with the law. The morality and ethics of business actors must also complement each other to create a fair and transparent trading environment. The author's suggestions are first, business actors should provide honest, complete and accurate descriptions of the products sold. Consumers need to increase awareness of their rights, how to transact safely in the marketplace, and understand how to file a complaint if they experience problems with their purchase. Second, in line with the caveat venditor doctrine, legal reforms to Indonesia's Consumer Protection Law are needed to recognise and clarify the responsibilities of businesses in online buying and selling transactions. Business actors must be fully responsible for the quality and safety of the products sold. Marketplaces must also have a mechanism to monitor the activities of business actors on their platforms and take firm action against business actors who violate consumer protection provisions.